Pengaruh Pengambilan Keputusan Dan Motivasi Terhadap Kepuasan Kerja Pegawai Badan Pengelola Pajak Dan Retribusi Daerah Kabupaten Musi Banyuasin Provinsi Sumatera Selatan - Indah Mawarni; Zein Ghozali; Imam Suroso; Nanda Revita; Marita Pratisila (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
The study conducted to look at the effect of decision making and motivation toward the working satisfaction of the employees of Badan Pengelola Pajak dan Retribusi Daerah Kabupaten Musi Banyuasin, South Sumatra Province aims to identify (a) how the decision making and motivation affected the working satisfaction of the employees of Badan Pengelola Pajak dan Retribusi Daerah Kabupaten Musi Banyuasin, South Sumatra Province, and (b) dominant variables affecting the working satisfaction of the employees of Badan Pengelola Pajak dan Retribusi Daerah Kabupaten Musi Banyuasin, South Sumatra Province. The method used in this study was causal method. The number of the population, 90 employees, was used as samples in this study. The technique of data collection was using questionnaires. To measure the effect among the variables, the multiple linear regression analysis was used. The research finding shows that simultaneous decision making and motivation affected the working satisfaction of the employees of Badan Pengelola Pajak dan Retribusi Daerah Kabupaten Musi Banyuasin, South Sumatra Province. The motivation variable partially affects dominantly the working satisfaction of the employees of Badan Pengelola Pajak dan Retribusi Daerah Kabupaten Musi Banyuasin, South Sumatra Province.